Penerapan Pendekatan Kontekstual dalam Pengembangan Buku Al-‘Arabiyyah Lil Induniysiyyin untuk Pembelajar Pemula - Muhammad Farhan Brilliant; Maghfiroh Maghfiroh; Namlul Wadi; Ahmad Rifa'i; Slamet Daroini (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
This study aims to analyze the contextual approach applied in the textbook Al-‘Arabiyyah Lil Indunisiyyin as an Arabic language learning material for beginner learners in Indonesia. The book was developed by the Muhammadiyah University of Malang, emphasizing the integration of local cultural context into the language content. Using a literature review method and a descriptive-analytical approach, this study found that all components of the book like vocabulary, dialogues, illustrations, and activities, systematically reflect the daily lives of Indonesian learners. The analysis reveals that the contextual approach employed in the book includes six key components: constructivism, inquiry, questioning, learning community, modeling, and reflection. These components contribute significantly to enhancing students' motivation, comprehension, and communicative competence. Additionally, the progressive structure of the material and the use of familiar visuals and themes demonstrate that this book serves not only as an instructional tool but also as a humanistic medium. Therefore, Al-‘Arabiyyah Lil Indunisiyyin can be considered an ideal model for the development of meaningful, relevant, and contextual Arabic teaching materials for beginners.